THE RELATIONSHIP BETWEEN MAN AND NATURE IN TRADITION AND IN THE FILM NARRATIVE (Philological Studies, 2023)
The focus of the research is the attitude towards tradition and its influence on the relation that man establishes with his environment. Taking the research of the media representation of the traditions related to the Epiphany holiday as a starting point, we look at the possibility of influencing man's attitude towards nature through artistic expression. In the text, I refer to the film "God exists, her name is Petrunia", which I consider to be receptive to analysis  because, although it is based on a real event, it develops its own story that raises a number of current social issues  related both to the past and the present that we live in. Such a setting of the film narrative allows for different interpretation concerning the issues related to the relationship between man and his environment. In the text, the analysis is based on the theoretical possibilities provided by the different  research and interpretationconcepts based on the ethno/eco-cultural perspective.